Hemorrhagic ascites endometriosis could be a cause: a case report - Nadia Abdelaaty Abdelkader; Ahmed F. Sherief; Enass Mohamed Soliman; Mahmoud Elsamman; Salah T. Fayed; Mohamed A. Sakr (SpringerOpen, 2021)
Abstract Background Endometriosis is a condition in which tissue similar to the lining inside the uterus (called "the endometrium") is found outside the uterus, where it induces a chronic inflammatory reaction that may result in scar tissue. Endometriosis with massive ascites causing abdominal distension and other symptoms simulating malignancy has been described in the literature. Case presentation A case of a 27-year-old woman who presented to the Ascites Study Group Tropical Medicine department Ain Shams University in collaboration with the Egyption Club of Ascites (ECA) with increased central abdominal contour, shifting dullness, and hemorrhagic transudate hypocellular ascites with no malignant cells and bilateral ovarian cysts. A long stepwise approach was conducted to the patient, and after exclusion of other causes of hemorrhagic ascites, the patient was prepared for laparoscopy. The diagnosis of endometriosis was made. The patient was discharged on goserelin acetate subcutaneous injection every 28 days with good response, and she regularly follows up with our study group on scheduled visits monthly according to her clinical status. Conclusions Endometriosis could be a possible cause of massive hemorrhagic obscured ascites. The unexplained infertility should increase the probability of the endometriosis.